2022
DOI: 10.1371/journal.pone.0273790
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological quality and antimicrobial susceptibility profiles of isolates of ready-to-eat raw minced meat from hotels and restaurants in Arba Minch, Ethiopia

Abstract: In Ethiopia, the bacteriological quality of ready-to-eat raw meat is of a great public health concern as it can serve as a source of meat-borne pathogens and worsen the transmission of antimicrobial resistant bacteria, and hence this cross-sectional study, done on 257 meat samples (ie., 169 beef, 50 mutton and 38 chevon) from randomly selected hotels and restaurants (n = 52). Approximately 25 gm of meat samples were taken bi-weekly and subjected to quantitative and qualitative analyses; antimicrobial susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Of the 76 isolated bacteria, the prevalence of MDR was 51 (67.1%) in meat and meat contact surfaces. Another study conducted in Ethiopia 38 also reported 60% of MDR isolates. The finding of this study was much higher than study conducted in Hawassa, Ethiopia 13 indicating that multidrug resistance differs significantly among different regions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Of the 76 isolated bacteria, the prevalence of MDR was 51 (67.1%) in meat and meat contact surfaces. Another study conducted in Ethiopia 38 also reported 60% of MDR isolates. The finding of this study was much higher than study conducted in Hawassa, Ethiopia 13 indicating that multidrug resistance differs significantly among different regions.…”
Section: Discussionmentioning
confidence: 85%
“…37 In this study, the isolates showed the highest rates of resistance to amoxicillin 67 (88.2%), ampicillin 67 (88.2%), penicillin 25 (89.3%), to erythromycin 43 (56.6%) and chloramphenicol 39 (51.3%). Many studies in Ethiopia 13,38,39 and abroad 40 have also reported high levels of resistance of some species to some antibiotics such as amoxicillin, ampicillin and penicillin. This high resistance to penicillin may be due to the continued use of penicillin derivatives in domesticated animals for slaughter.…”
Section: Discussionmentioning
confidence: 99%
“…Foodborne illnesses and infections are prominent global health issues that pose significant risks to human health and lives. Researchers have recognized more than 250 foodborne diseases [1]. Foodborne disease not only affects the physical health and well-being of individuals, but it also has a substantial impact on the social and economic productivity of nations [2].…”
Section: Introductionmentioning
confidence: 99%